2014
DOI: 10.2337/db14-0721
|View full text |Cite
|
Sign up to set email alerts
|

Acute Activation of Cannabinoid Receptors by Anandamide Reduces Gastrointestinal Motility and Improves Postprandial Glycemia in Mice

Abstract: The endocannabinoid system (ECS) is associated with an alteration of glucose homeostasis dependent on cannabinoid receptor-1 (CB1R) activation. However, very little information is available concerning the consequences of ECS activation on intestinal glucose absorption. Mice were injected intraperitoneally with anandamide, an endocannabinoid binding both CB1R and CB2R. We measured plasma glucose and xylose appearance after oral loading, gastrointestinal motility, and glucose transepithelial transport using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The second proposed target for T2D probiotic therapy is the eCB system, already discussed in relation to obesity 226. CB 1 is involved in gut permeability and modulation of the gut microbiota appears to yield similar responses to CB 1 antagonists, upregulating expression and correcting the localisation of intestinal epithelial tight junction proteins, occludin and zonula occludens1 227.…”
Section: Probiotics As Diabetic Therapiesmentioning
confidence: 99%
“…The second proposed target for T2D probiotic therapy is the eCB system, already discussed in relation to obesity 226. CB 1 is involved in gut permeability and modulation of the gut microbiota appears to yield similar responses to CB 1 antagonists, upregulating expression and correcting the localisation of intestinal epithelial tight junction proteins, occludin and zonula occludens1 227.…”
Section: Probiotics As Diabetic Therapiesmentioning
confidence: 99%
“…Central CB1 stimulation leads to increase food intake (Di Marzo et al, 2001; Silvestri and Di Marzo, 2013), and CB1 blockade induces weight loss (Van Gaal et al, 2005). Conversely, peripheral CB1s play an important role in glucose homeostasis by modulating lipogenesis in liver and adipose tissues (Cota et al, 2003; Matias et al, 2006; Osei-Hyiaman et al, 2005), glucose uptake in skeletal muscle (Esposito et al, 2008) and motility of the gastrointestinal tract (Izzo and Sharkey, 2010; Troy-Fioramonti et al, 2014). While most researchers agree that pancreatic beta (β) cells also contain CB1 (Bermúdez-Silva et al, 2008; Kim et al, 2011; Starowicz et al, 2008), its exact role in insulin secretion remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of CB1 stimulates G i/o , which inhibits AC activity and cAMP synthesis (Turu and Hunyady, 2010). In mouse, enteroendocrine cells express CB1 receptor (Sykaras et al, 2012), and its activation inhibits GIP secretion (Moss et al, 2012; Troy-Fioramonti et al, 2014), which suggests that blockade of CB1 would at least indirectly stimulate insulin secretion through GIPR. Several recent studies have suggested a potential interaction between incretin receptors and CB1, particularly with regard to food intake (E.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that hyperinsulinemia does not require elevation of plasma anandamide. Since acute in vivo treatment with anandamide has been shown to decrease intraperitoneal glucose tolerance in wild type mice [ 34 , 35 ] but not in CB1R -/- mice [ 34 ], there is a possibility that elevation of plasma anandamide levels may be a cause rather than consequence (compensatory signal) of insulin resistance. Future studies exploring the chronic effect of anandamide treatment in vivo may help to elucidate this question.…”
Section: Discussionmentioning
confidence: 99%